SOIL PORE SIZE DISTRIBUTION AT DIFFERENT CARBONATE MINERALS CONTENT - & Naji, Mahdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Pore space, especially pore size distribution is one of the important properties affecting soil infiltration, hydraulic conductivity, and water retention. To examine the effect of carbonate minerals on pore size distribution, soil material with loam texture was used to prepare nine soil materials containing wide range of carbonate minerals (3.2 - 352 g kg-1). The soil-water retention curve (θ(ψ)) was estimated. Computer program (RETC code) was used to determine the best-fit for experimental data of water potential versus volumetric water content which have nonlinear relationship to determine the parameter of van Genuchten equation [α, n and m with m=1-(1/n)]. The capillary rise equation (young-laplace equation) was used to estimate the effective pore diameter (D). The results show that pore space was affected by carbonate minerals contents. Air pores (> 30 μm) increased 1.4 fold with increasing carbonate minerals at the same time capillary pores filled with water (< 30 μm) decreased by 1.3 folds. The relative of water volume to total soil volume ranged between 0.27 and 0.21 cm3cm-3 for carbonate minerals content 3.2 and 352 g kg-1 respectively. At 10 kPa the amount of water lost increased with increasing carbonate minerals content, where soil sample with 352 g.kg-1 carbonate minerals lost water more than soil sample with 3.2 g.kg-1 carbonate minerals by 42%. The percentage of pores (< 30 μm) ranged from 67% to 79% and the pores (> 30 μm) ranged from 33% to 21%. It can be concluded that high carbonate minerals content in the soil led to change in pore size distribution, where air-filled pores increased and capillary pores filled with water (water holding capacity) decreased at different degree from sample to another.